(3GdeQCI aj GdbGfhf GdLfGFj (B: s (3OQGSI ebGQfI (B/ s - (3eMeO YHOGdQMef YHOGdeMSfs; (3CSGeI MSfjf YHjO s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2012)
(3JfGhd GdHMK ehVhY GdeQCI aj GdbGfhf GdLfGFj(B: (3h Pdc HJhVjM deGgjI GdeQBI aj bGfhf GdYbhHGJ(B: (3ef NdGd JfGhd GdMeGjI GdLfGFjI ddeQCI HTbjgG GdHOfjI h GdeYfhjI(B: (3aVdG Yf GSJYQGVfG deGgjI GdeSFhdjI GdLfGFjI ddeQCI aj LQGFe GdRfG h GdELgGV h GdHZGA(B. (3h GSJYQVfG GdeQCI aj bGfhf GdELQGAGJ GdLfGFjI ef NdGd eQMdI GdeMGceI GdLfGFjI(B: (3h GdbGYOI GdYGeI ddJaJjT(B: (3h JfajP GdYbhHI Ydi GdeQCI OGNd GdeDSSGJ GdYbGHjI(B: (3h GfJgjfG Edi HYV GdJhUjGJ(B: (3CgegG(B: (3GdJhUjI HJYOjd fU GdeGOI (B((3267(B) (3ef bGfhf GdYbhHGJ(B: (3h JYOjd cGaI GdfUhU GdJj JejR Hjf GdQLd h GdeQCI aj bGfhf GdYbhHGJ(B: (3aVdG Ydi EdZGA cGaI CTcGd GdJejjR aj eLGd GdELQGAGJ GdLfGFjIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFj, (B2012s
(3HHdjhLQGajG(B: (3UaMGJ (B331-346s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3ecGfI GdeQCI aj GdTQjYI GdESdGejIs; (3GdeQCI aj Xd GdehGKjb hGdGJaGbjGJ GdOhdjIs; (3GdeQCI ai bGfhf GdYbhHGJs; (3GdeUdMI eMd GdMeGjI GdLfGFjIs; (3GdMeGjI GdLfGFjI dMjGA GdeQCI s; (3MQeI GdMjGI GdNGUI ddeQCIs; (3MQeI GdMjGI aj GdTQjYI GdESdGejIs; (3GdeSFhdjI GdLfGFjI ddeQCI aj LQjeI GdRfGs; (3GdeSFhdjI GdLfGFjI ddeQCI aj LQjeI GdELgGVs; (3GdeSFhdjI GdLfGFjI ddeQCI aj LQjeI GdHZGAs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs